Characterizing tropical cyclone from altimeter wind speed profile - Abdullah, Nik Raisyha Nurfarain; Sharoni, Syarawi M. H.; Md Reba, Mohd Nadzri; Ayob, Nurul Najwa; Abir, Ismail Ahmad; Hwee, San Lim; Ramli, Muhammad Zahir (Taylor and Francis, 2025)
Tropical cyclones (TC) rank among the most destructive natural phenomena, with wind speed measurements at 10 meters above sea surface (U10) are crucial for understanding their dynamics. Although operational altimeter products previously faced challenges in U10 accuracy under extreme TC conditions, recent advances in estimation models now enable reliable characterization of TC wind structures. This study analyze four TCs using data from Jason-2 and Jason-3 satellites alongside IBTrACS records, deriving U10 profiles and key storm characteristics including storm centers, radii of inner/outer winds, and maximum sustained wind (MSW). By implementing an enhanced U10 estimation model, this study demonstrates the feasibility of characterizing TC wind structures with fine along-track resolution. The methodology involves identifying storm centers from U10 peaks, defining radii thresholds for wind regions, and comparing results with best-track data. Findings show strong agreement in storm center location, wind radii, and characteristics. Altimeters offer unique advantages such as high along-track resolution and simultaneous sea-state observations, providing critical insights into near- center TC dynamics. While limitation persist in swath coverage and high wind regime performance, this work highlights altimeters potential to complement existing TC monitoring systems by enhancing fine-scale and sea-state analysis.